An Economic and Policy Analysis of a District Heating System Using Corn Straw Densified Fuel: A Case Study in Nong’an County in Jilin Province, China - Shizhong Song; Pei Liu; Jing Xu; Linwei Ma; Chinhao Chong; Min He; Xianzheng Huang; Zheng Li; Weidou Ni (Energies, 2016)
The development of district heating systems of corn straw densified fuel (CSDF-DHS) is an important option to promote the use of bioenergy on a large scale for sustainable development, especially in China. At present, China’s biomass densified solid fuel (BSDF) development lags behind previously planned target, main barriers of which are economic and policy support problems. Accurate case studies are key to analyze these problems. This manuscript takes Nong’an County in Jilin Province of China as an example to establish a techno-economic model to evaluate the economic performance of a CSDF-DHS under two policy scenarios. It calculates the economic performance under a benchmark market scenario (BMS) and the current policy scenario (CPS) and analyzes the influence of various policy instruments, including subsidies, carbon trading, and preferential taxation. The results indicate that: (1) The CSDF-DHS option is not competitive under the BMS or CPS compared to the traditional energy system based mainly on coal and liquefied petroleum gas; (2) Comparatively, the economic performance of corn straw briquette fuel (CSBF) is better than that of corn straw pellet fuel (CSPF); and (3) further policy support can make CSDF-DHSs competitive in the market, especially with subsidies for concentrated heating services and CSDF, carbon trading, and economic compensation to reduce the profit margin of enterprises, which can make both CSPF-DHSs and CSBF-DHSs competitive. The research results could provide scientific basis for relevant policy making and project decision.